Exploring the value of brands on the montenegrin bottled spring water market - Jankovic, Marija (Applied Studies in Agribusiness and Commerce, 2013)
The branding strategy is based on future goals relating to clients, aimed at increasing awareness of the brand, creating a positive brand image and establishing a preference for the brand and ensuing brand loyalty. A brand is a very important factor for competitiveness and establishes a leadership position in the market, given the major impact that this form of intellectual property has on the perception of consumers and the success of innovative products on the market. The bottled water market has increased by about 35% in the last five years on the global level, dictated by young consumers who are becoming increasingly aware of the significance of proper nutrition in maintaining health. The research presents qualitative information on the market value of bottled water brands, the general characteristics of retailers, as well as on their target customers. The main task of this paper is to confirm the usefulness of marketing research in modern business as well as to present the benefits of brand value measurement to current or future brand owners. It is to be hoped that the results presented in this paper may serve as a good basis for upgrading marketing activities, based on a better understanding of target customers and their particular needs, through better communication for the purpose of stronger corporate branding.